Variability of microphytoplankton community composition in response to oceanographic drivers in the coastal upwelling area off central Chile - Masotti, Italo; Aparicio-Rizzo, Pilar (Revista de Biología Marina y Oceanografía, 2024)
In coastal upwelling areas, the microphytoplankton community comprises two main groups, diatoms and dinoflagellates. However, neither group is uniform because physical-chemical and biological interactions can affect the community structure. In this work, the composition of the microphytoplankton community was analyzed at a fixed station located in Valparaíso Bay (~32°-33°S) using the Reynolds C-S-R model. In the bay, monthly variation of the microphytoplankton community occurred due to nutrient availability (nitrate-NO3-, silicate-SiO44-, and N/Si ratio), and water temperature, driven by upwelling activity. Three main communities were observed. The first one comprised neritic R diatoms such as Asterionellopsis glacialis, Chaetoceros radicans, and Chaetoceros tortissimus from late winter to early summer (August-December), when upwelling activity occurred with the ascent of cold and nutrient-rich water. In addition, dinoflagellates such as Protoperidinium brochii, Protoperidinium pellucidum, and Preperidinium meunieri were identified as part of this community. Secondly, S/R-S dinoflagellates such as Tripos furca var. berghii, Ceratium tripos f. tripodioides, Prorocentrum gracile, and Protoperidinium steinii were predominant under thermal stratification conditions from summer to autumn (January-April) together with C-R pennate diatoms such as Navicula sp. and Thalassionema nitzschioides. Finally, a community including neritic R-C/R diatoms such as Leptocylindrus danicus, Guinardia delicatula, Detonula pumila, Pseudo-nitzschia australis, Skeletonema costatum, Thalassiosira mendiolana, and Chaetoceros sp. was present throughout the year with no remarkable connection to any oceanographic conditions. Although upwelling activity constitutes the main driver of microphytoplankton community succession in the bay, biological interactions appear to play also a role, being necessary a deeper study under an ecological perspective. Key words: Microphytoplankton, community composition, diatoms, dinoflagellates, upwelling